Experience-Based Heterogeneity in Expectations and Monetary Policy - Lucas Radke; Florian Wicknig (ZBW - Leibniz Information Centre for Economics, 2021)
The present paper studies the effect of monetary policy on inflation and output within a New Keynesian model with Experience-Based Learning (EBL) that renders expectations heterogeneous across age groups. Under EBL, the age-distribution directly affects the composition of aggregate expectations which gives rise to a novel channel by which the demographic structure of an economy affects monetary policy: the Experience Channel. Relative to models with homogeneous and age-independent expectations, we show that EBL weakens the pass-through of monetary policy on aggregate demand. This affects monetary policy transmission in two ways. First, the impact response of inflation and output to monetary policy shocks is less pronounced since the response of expectations under EBL is muted. Second, the response of inflation is more persistent, since the interest rate sensitivity of aggregate demand is weaker. Moreover, EBL changes the classical monetary policy trade-off between output and inflation stabilisation under supply shocks relative to models with ageindependent expectations. First, for a given inflation volatility, output is always less volatile due to the reduced sensitivity of expectations to monetary policy. Second, under EBL, the trade-off becomes more severe in ageing economies. We show that this effect is largely driven by the Experience Channel.
Keywords: D84; E32; E37; E52; E70; 330; Monetary Policy; Learning; Heterogeneous Expectations; ExperienceEffects; Demography